PELAKSANAAN & EVALUASI PERKULIAHAN PENGENALAN TIPOGRAFI SECARA DARING SEBAGAI RESPON TERHADAP PANDEMI COVID-19 - Brian Alvin Hananto (Universitas Mercu Buana, 2021)
Typography is an essential skill for visual communication design. Teaching foundational typography is often a challenge due to its nature, and with the COVID-19 Pandemic, adapting the teaching for typography has been a challenge. To develop the online teaching of typography, the author conducted classroom action research on the Introduction to Typography course on Universitas Pelita Harapan in the 2020/2021 academic year. There were 49 students in three classes that participate in this research. The class consists of four learning projects: Alphabetography, Type as Image, Typographic Contrast, and Quotes Poster Design; and also 10 Quizzes. After one semester, the result and grades of the 2020/2021 students increased compared to the 2019/2020 students. The author hopes that the classroom action research can become a basis for the next teaching and research cycle.